Incidence, clinical spectrum, and immunotherapy of non-ischemic cerebral enhancing lesions after endovascular therapy - Antonios Bayas; Monika Christ; Ansgar Berlis; Markus Naumann; Michael Ertl; Felix Joachimski; Mona Müller; Julia Welzel; Lisa Ann Gerdes; Klaus Seelos; Christoph Maurer (Therapeutic Advances in Neurological Disorders, 2022)
Background: Symptomatic and asymptomatic delayed non-ischemic cerebral enhancing (NICE) lesions in magnetic resonance imaging (MRI) have been reported as a rare complication after endovascular therapy (EVT) in recent years with incidence rates between 0.05% and 0.9% in most studies. Information on long-term clinical course and immunotherapies is scarce or has not been reported in detail in the literature. Objective: Aims of our study were to assess the incidence of NICE lesions in patients after cerebral EVT over a period of more than 12 years, describe clinical and EVT characteristics, and immunotherapies applied. Methods: A retrospective chart review of all patients treated by endovascular therapy for symptomatic or asymptomatic aneurysms at the University Hospital of Augsburg from May 1, 2008 to December 31, 2020 was performed. Patients were identified retrospectively and followed-up prospectively where appropriate. In addition, one case treated at another institution was included. Results: Five out of 746 patients, 0.67%, developed NICE lesions after EVT, all with non-ruptured aneurysms and all symptomatic upon detection of NICE lesions by MRI. In total, the disease course of 6 female patients is reported. Symptoms occurred after a mean time of 15 days (±13.42, SD) after EVT with headache (6/6 patients), focal neurological signs (6/6 patients), epileptic seizures (2/6 patients) and cognitive deficits (3/6 patients). All 6 patients received glucocorticosteroids (GCS), 1/6 azathioprine (AZA), 4/6 mycophenolate mofetil (MMF), 1/6 methotrexate (MTX), 1/6 rituximab (RTX), 2/6 cyclophosphamide (CYC) and 3/6 tocilizumab (TCZ). A treatment response could be observed for GCS, TCZ and MMF (in two of four cases), RTX and AZA did not result in disease stabilization. Conclusions: Delayed NICE lesions are a rare complication after EVT, requiring immunotherapies in all patients reported here. Physicians should be aware of this disorder in case of new symptoms or contrast enhancing lesions after EVT.